2007
DOI: 10.1634/theoncologist.12-8-942
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Activates Notch-1 Signaling and Regulates the Neuroendocrine Phenotype in Carcinoid Cancer Cells

Abstract: Carcinoid tumors are neuroendocrine malignancies that frequently metastasize and secrete hormones that cause debilitating symptoms in patients. In this study we report the effects of valproic acid (VPA), a drug long used for the treatment of epilepsy, on the growth and neuroendocrine phenotype of human carcinoid cancer cells. VPA treatment of gastrointestinal and pulmonary carcinoid cells resulted in a dose-dependent inhibition of cancer cell growth. Western blot analysis revealed degradation of cyclin D1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 45 publications
11
149
1
Order By: Relevance
“…In a recent study valproic acid (a NOTCH activator) treatment of gastrointestinal and pulmonary neuroendocrine tumor cell lines resulted in a dose-dependent inhibition of cancer cell growth and also increased levels of full-length NOTCH1 and the active NOTCH1 intracellular domain 9. 22 This study underscores the need for a site-based critical assessment of signaling pathways, when designing clinical trials for gastrointestinal neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 84%
“…In a recent study valproic acid (a NOTCH activator) treatment of gastrointestinal and pulmonary neuroendocrine tumor cell lines resulted in a dose-dependent inhibition of cancer cell growth and also increased levels of full-length NOTCH1 and the active NOTCH1 intracellular domain 9. 22 This study underscores the need for a site-based critical assessment of signaling pathways, when designing clinical trials for gastrointestinal neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 84%
“…Given that VPA has been reported to activate Notch1 signaling in several NET cell lines (13,20), we were interested in determining the ability of VPA to activate Notch1 signaling in SCLC cells. To assess this, we measured protein levels of full-length Notch1 and NICD after treatment with various concentrations of VPA.…”
Section: Vpa Induces Notch1 Signaling In Sclc Cellsmentioning
confidence: 99%
“…We have previously shown that Notch1 signaling is minimal or absent at baseline in several NET cell lines, and that expression of exogenous Notch1 via an inducible construct inhibits NET cell growth (6,14). Additionally, VPA has been reported to activate Notch1 signaling in neuroblastoma, carcinoid, and medullary thyroid cancer cells (13,19,20). We hypothesized, then, that VPA may also activate Notch1 signaling in SCLC cells with subsequent anti-tumor effects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some researches revealed up-regulation of Bak protein expression, degradation of cyclin D1 and an increase in cyclin-dependent kinases p21 and p27 after sodium valproate treatment. In addition, sodium valproate also increased the levels of full-length Notch-1 and active Notch-1 intracellular domain, which intern inhibit proliferation and induced apoptosis of neoplasm (Greenblatt et al, 2007;Fortunati et al, 2008;Platta et al, 2008). Sami et al in cervical cancer found that sodium valproate can increase the expression of histone H3 acetylation and up-regulate p21 expression (Sami et al, 2008).…”
Section: 6429 Effects Of Sodium Valproate On the Growth Of Human Ovamentioning
confidence: 97%